2016
DOI: 10.1002/cjoc.201600129
|View full text |Cite
|
Sign up to set email alerts
|

A Turn‐On Fluorescent Probe for Highly Selective and Sensitive Detection of Palladium

Abstract: A novel turn-on fluorescent probe for the detection of palladium has been designed. The probe can selectively and sensitively detect palladium in solution, and the limit of detection was calculated to be 11.4 nmol•L 1. Furthermore, the probe was successfully used for fluorescence imaging of palladium in living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 55 publications
(42 reference statements)
0
3
0
1
Order By: Relevance
“…Zhou et al (in 2016) reported 142 probe 24 to detect Pd( ii ) ions by incorporating propargyl moiety with resorufamine dye via a carbamate linker (Fig. 18).…”
Section: Probes For Pd Ionsmentioning
confidence: 99%
“…Zhou et al (in 2016) reported 142 probe 24 to detect Pd( ii ) ions by incorporating propargyl moiety with resorufamine dye via a carbamate linker (Fig. 18).…”
Section: Probes For Pd Ionsmentioning
confidence: 99%
“…Other metal ions are also harmful to humans, such as palladium. [56] Xu et al designed a fluorogenic probe Cy202PD (probe 17), which consists of a QCy7 fluorophore and a propargyl ether trigger (Figure 11). [31] In the presence of Pd 2 + , it exhibits a fluorescence enhancement at 689 nm with a detection limit of 0.52 μM, indicating that probe 17 has the ability to selectively and sensitively detect palladium ions.…”
Section: Other Biomarkers Activated Qcy7-based Fluorogenic Probesmentioning
confidence: 99%
“…We imagined that loading Na 2 CO 3 on ZSM-5 could further improve the activity and stability of the catalyst while retaining their original respective advantages (the chemical reaction equation is shown in Scheme 1) based on our previous research. 36,37 In addition, the recycling of catalysts could also save a large amount of energy and production costs, improving the practical application values of resource utilization of WCO.…”
Section: Introductionmentioning
confidence: 99%